1979
DOI: 10.1121/1.382973
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of the effects of various laryngeal configurations on the acoustics of phonation

Abstract: Simulation of glottal volume flow and vocal fold tissue movement was accomplished by numerical solution of a time-dependent boundary value problem, in which nonuniform, orthotropic, linear, incompressible vocal fold tissue media were surrounded by irregularly shaped boundaries, which were either fixed or subject to aerodynamic stresses. Spatial nonuniformity of the tissues was of the layered type, including a mucosal layer, a ligamental layer, and muscular layers. Orthotropy was required to stabilized the voca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
121
0
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(128 citation statements)
references
References 0 publications
3
121
0
4
Order By: Relevance
“…This model allows for simulation of the vibrational pattern of the vocal folds in both the coronal and traverse planes. A further step up in complexity came with a continuum mechanics model [21] and a more recent finiteelement model [22] both of which provide a precise physiological and mechanical representation of the tissue layers of the vocal folds without lumping large anatomical regions into a few mass elements. Their large number of degrees of freedom allows for detailed study of the complex vibratory pattern observed in human vocal folds.…”
Section: Figmentioning
confidence: 99%
“…This model allows for simulation of the vibrational pattern of the vocal folds in both the coronal and traverse planes. A further step up in complexity came with a continuum mechanics model [21] and a more recent finiteelement model [22] both of which provide a precise physiological and mechanical representation of the tissue layers of the vocal folds without lumping large anatomical regions into a few mass elements. Their large number of degrees of freedom allows for detailed study of the complex vibratory pattern observed in human vocal folds.…”
Section: Figmentioning
confidence: 99%
“…Due to the technical challenges of in vivo experiments, mostly theoretical studies have been used to understand the influence of neuromuscular activation and laryngeal posture on phonation dynamics. For example, Titze and Talkin (1979) found that fundamental frequency (F0) of phonation was primarily controlled by longitudinal tension (associated with glottal length) and that trans-glottal pressure was less effective. Actively controlled muscular contraction appears to provide the necessary flexibility for the glottis to allow a broad F0 range and the many varieties of phonation (Titze, 1994;Titze and Talkin, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Titze and Talkin (1979) found that fundamental frequency (F0) of phonation was primarily controlled by longitudinal tension (associated with glottal length) and that trans-glottal pressure was less effective. Actively controlled muscular contraction appears to provide the necessary flexibility for the glottis to allow a broad F0 range and the many varieties of phonation (Titze, 1994;Titze and Talkin, 1979). However, the interactions of ILMs and their influence on phonatory posture and resulting dynamics remain poorly understood and have not been systematically investigated in experimental in vivo models.…”
Section: Introductionmentioning
confidence: 99%
“…Mauleón y Gurlekian (2001), compararon la articulación de consonantes oclusivas en el habla y en el canto, y encontraron que a diferencia del habla en el canto persistía la vibración glótica durante la fase de oclusión de estas consonantes. La articulación es entonces, uno de los medios técnicos de alto valor expresivo que el cantante maneja con sutileza y en forma significativamente diferenciada con respecto al habla, Más aún, dada la estrecha relación entre articulación y resonancia (Sundberg, 1974), existen aún variaciones más sutiles que el can-tante puede imponer al sonido, dependiendo de la configuración del tracto vocal inferior, por ejemplo, variando la altura relativa de la laringe puede conseguirse un timbre con más o menos armónicos graves, y una de las estrategias de que se vale para lograr esto es la forma en que realiza la inspiración previa al canto (Gramming et al, 1993;Watson y Hixon, 1985;Sundberg y Nordstöm, 1983, 1987Titze y Talkin, 1979). Pero, la utilización de este tipo de recursos vocales (variación en la posición de la laringe o el vibrato, o cambios articulatorios) está guiada generalmente por el uso "consciente" de mecanismos cuasi-reflejos que el cantante maneja generalmente de forma intuitiva, recurriendo a la estrategia de "pensar" o imaginar el color vocal deseado o la emoción afín a las características sonoras que desea.…”
Section: Los Movimientos De Ejecución Del Cantanteunclassified